FORMULASI DAN UJI EFEKTIVITAS ANTIBAKTERI TERHADAP SEDIAAN Deodorant Spray EKSTRAK ETANOL BATANG SERAI WANGI (Cymbopogon nardus L.) TERHADAP BAKTERI Staphylococcus aureus - Evi Deviana Gultom (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2026)
Abstract Body odor is one of the personal hygiene problems caused by bacterial activity such as Staphylococcus aureus on sweat. Continuous use of chemical-based deodorants may cause skin irritation; therefore, natural alternatives are needed. This study aims to formulate and evaluate the antibacterial effectiveness of a deodorant spray preparation made from citronella (Cymbopogon nardus L.) stem ethanol extract. The extract was obtained using the maceration method with 96% ethanol, followed by phytochemical screening to identify active compounds. The deodorant spray was formulated in three extract concentrations—5%, 10%, and 15%—and evaluated for organoleptic properties, pH, drying time, spray power, and homogeneity. The antibacterial effectiveness test against Staphylococcus aureus was carried out using the disc diffusion method. The results showed that all formulas met the physical evaluation requirements of deodorant preparations. The largest inhibition zone was observed in the formula containing 15% extract, with a diameter of 16.33 mm, categorized as strong inhibitory activity. Therefore, the ethanol extract of Cymbopogon nardus stem has the potential to be used as an active ingredient in natural antibacterial deodorant spray formulations against Staphylococcus aureus.